Becoming the role model: youth recreation leaders, occupational choice and a will to include. Issue 6 (2nd November 2018) - Fejes, Andreas; Dahlstedt, Magnus
ABSTRACT: The aim of this article is to analyse how a discourse on the role model operates in youth recreational work. Drawing on Michel Foucault's concepts of subjectivity, discourse and power-knowledge, the article analyses interviews with youth recreation leader students enrolled at a folk high school, and their talk about occupational choice. The analysis illustrates how a discourse on the role model emerges and operates through the ways students' descriptions of 'being' and 'doing' intersect with their becoming as role models. The analysis raises several important questions. Should youth recreational work only target those young people who are already marginalised? Are there other subject positions than the role model, available to take up in youth recreation work? Are experiences of marginalisation necessary in order for a desirable youth recreation leader to emerge?